2009
DOI: 10.1095/biolreprod.109.077016
|View full text |Cite
|
Sign up to set email alerts
|

Significant Improvement in Cloning Efficiency of an Inbred Miniature Pig by Histone Deacetylase Inhibitor Treatment after Somatic Cell Nuclear Transfer1

Abstract: The NIH miniature pig was developed specifically for xenotransplantation and has been extensively used as a large animal model in many other biomedical experiments. However the cloning efficiency of this pig is very low (less than 0.2%) and this has been an obstacle to the promising application of these inbred swine genetics for biomedical research. It has been demonstrated that increased histone acetylation in somatic cell nuclear transfer (SCNT) embryos, by applying histone deacetylase inhibitors (HDACi) suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
178
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(187 citation statements)
references
References 51 publications
5
178
2
Order By: Relevance
“…the efficiency of 1.3-2.4%, even though they used Fs as a donor cells Zhao et al, 2009). Because cloned embryos were treated with drugs that can improve reprogramming prior to embryo transfer in the Zhao et al study, and preselected high-quality oocytes were used for cloning in the Kim et al study, these could be the main reasons causing the difference in cloning efficiency between our study and their studies.…”
Section: Figmentioning
confidence: 62%
“…the efficiency of 1.3-2.4%, even though they used Fs as a donor cells Zhao et al, 2009). Because cloned embryos were treated with drugs that can improve reprogramming prior to embryo transfer in the Zhao et al study, and preselected high-quality oocytes were used for cloning in the Kim et al study, these could be the main reasons causing the difference in cloning efficiency between our study and their studies.…”
Section: Figmentioning
confidence: 62%
“…We thus thought that this may underlie the discrepancy of in vivo developmental capacity of NT embryos derived from mouse iPSCs and piPSCs. Previous studies have also demonstrated that the state of histone acetylation in somatic cell NT embryos, significantly impacts the developmental competence in several species [9].…”
Section: Dear Editormentioning
confidence: 95%
“…Therefore, in the second round of experiments, we took the following measures to attempt to improve the developmental capacities of cloned embryos: 1) silence the exogenous transcription factors through spontaneous differentiation of piPSCs before they are used as donor cells; 2) increase histone acetylation by treating the constructed embryos with Scriptaid, a novel histone deacetylase inhibitor that can improve cloning efficiency through increasing transcriptional activity [9]. To silence exogenous transcription genes, piPSCs were allowed to spontaneously differentiate for 4-6 days.…”
Section: Dear Editormentioning
confidence: 99%
“…FFs were established as previously described (Kragh et al, 2005;Onishi et al, 2000;Zhao et al, 2009). Briefly, fetuses obtained 40 days after insemination were decapitated, eviscerated, and cut into small pieces with fine scissors in phosphate-buffered saline (PBS).…”
Section: Primary Cell Lines Establishment and Donor Cells Preparationmentioning
confidence: 99%